Analisis Kualitas Ruang Publik RTH dan RPTRA Kalijodo - Hidayat, Andhika Rizky; Khuluk, Nazaruddin (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2021)
After several years of operation, it can be seen how the lack of proper care and maintenance has made thequality of this public space less comfortable for the community. Many facilities are damaged and notmaintained, judging by the quality of the Kalijodo Green Open Space and RPTRA from the aspects of needs,rights and meaning. And to find out the quality of Kalijodo RTH and RPTRA from these aspects. The methodused is a qualitative descriptive method with a case study approach. Qualitative methods are socialresearch steps to obtain descriptive data in the form of words and pictures. Based on all aspects (needs,rights and meanings) in RTH has a good quality level with a percentage of 62.6% and RPTRA has a goodquality level with a percentage of 67.3%. Therefore there are still many shortcomings such as having topay attention to the condition of several facilities, there needs to be improvement so that visitors can feelcomfortable while relaxing in the open space. and needs to be improved again in terms of care andmaintenance of its facilities. This research is expected to be a reference for evaluating public space, so thatit can become a guideline for the progress of public space quality standards